2010
DOI: 10.1177/1947601910395583
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the YES1 Kinase as a Therapeutic Target in Basal-Like Breast Cancers

Abstract: Normal cellular behavior can be described as a complex, regulated network of interaction between genes and proteins. Targeted cancer therapies aim to neutralize specific proteins that are necessary for the cancer cell to remain viable in vivo. Ideally, the proteins targeted should be such that their downregulation has a major impact on the survival/fitness of the tumor cells and, at the same time, has a smaller effect on normal cells. It is difficult to use standard analysis methods on gene or protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…To assess the feasibility of the use of miR-125a-3p as a regulator of Fyn expression in various cancerous cells, we examined the expression of Fyn mRNA in miR-125a-3p-overexpressing cancer cell lines: MNT-1 (melanoma cancer), U2OS (osteosarcoma), MDA-MB-231, MCF-7 and SKBR3 (breast cancers), PC3 (prostate cancer) and HeLa (cervical cancer). The role of Fyn in tumor progression or its overexpression has already been illustrated in these cancer cell lines, with the exception of osteosarcoma (Teutschbein et al, 2009;Huang et al, 2003;Zhao et al, 2011;Posadas et al, 2009;Bilal et al, 2010;Yadav and Denning, 2011). We found that the expression of Fyn mRNA was reduced in all the examined cell lines, except HeLa cells (Fig.…”
Section: Mir-125a-3p Negatively Regulates the Activity Of Proteins Dosupporting
confidence: 50%
“…To assess the feasibility of the use of miR-125a-3p as a regulator of Fyn expression in various cancerous cells, we examined the expression of Fyn mRNA in miR-125a-3p-overexpressing cancer cell lines: MNT-1 (melanoma cancer), U2OS (osteosarcoma), MDA-MB-231, MCF-7 and SKBR3 (breast cancers), PC3 (prostate cancer) and HeLa (cervical cancer). The role of Fyn in tumor progression or its overexpression has already been illustrated in these cancer cell lines, with the exception of osteosarcoma (Teutschbein et al, 2009;Huang et al, 2003;Zhao et al, 2011;Posadas et al, 2009;Bilal et al, 2010;Yadav and Denning, 2011). We found that the expression of Fyn mRNA was reduced in all the examined cell lines, except HeLa cells (Fig.…”
Section: Mir-125a-3p Negatively Regulates the Activity Of Proteins Dosupporting
confidence: 50%
“…Three of the regions were small, containing just one gene: chr17 - RAB11FIP4; chr20 - MACROD2, overexpression of this gene has been implicated in oestrogen-independent growth [27]; and chrX - KLF8, oncogenic in ovarian but not breast cancer cell lines [28]. There was also a similar region on chr18, that was more common in both pure and inv-cLCIS compared to ILC, containing YES1, a SRC proto-oncogene that has recently been identified as a possible therapeutic target in basal breast cancer [29]. It is possible that these regions contain genes that hinder development of the invasive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examining the downregulation of Yes1 by shRNA found significant effects on cell survival and growth for basal-like and Her2-positive breast cancers. 10 In a similar manner, the knock down of Yes1 expression with shRNA in both embryonal and alveolar rhabdomyosarcoma cell lines (RD and RH30) was found to significantly inhibit cell growth in vitro , thereby implicating Yes1 as a potential therapeutic target for this aggressive cancer. 11 Despite the potential for Yes1 to be a target for the above-described cancers, there are very few reports on the identification of potent and selective inhibitors of Yes1 kinase.…”
mentioning
confidence: 86%